Perencanaan Arsitektur Organisasi Untuk Mendukung Pengembangan Sistem Informasi Perguruan Tinggi - Ade Mulyana; Septian Cahyadi; Anton Sukamto (Forum Dosen Indonesia, 2019)
Strategies and policies in a profit-oriented organization have a social mission (public service) that prioritizes customer service. The development of information systems and information technology will have an impact on increasingly competitive competition, this also applies in the world of education, especially for higher education institutions that are managed by the community (private), requiring managers to build and develop information systems to help business activities, achieve organizational goals. and services for stakeholders. Enterprise Architecture Planning (EAP) as a method or frame of reference for building an information architecture. EAP is an architectural planning method that is oriented to business needs which consist of data architecture, applications, and technology as well as an implementation plan of the architecture that has been created to support business activities for the achievement of an organization's mission. Keywords: Enterprise Architecture, information architecture, business activities.